Emotional dissonance and mental health among home-care workers: A nationwide prospective study of the moderating role of leadership behaviors - Håkon A Johannessen; Morten Birkeland Nielsen; Rigmor Harang Knutsen; Øivind Skare; Jan Olav Christensen (Scandinavian Journal of Work, Environment & Health)

(untitled)
OBJECTIVES: Evidence suggests that emotional dissonance, the imbalance between true feelings and those displayed to meet work standards, heightens the risk of mental distress. In nursing occupations, exerting such emotional effort is a part of the job role. Drawing from the job demands–resources model, high-quality leadership is a resource that may assist employees in coping with stressors. We examined whether quality of leadership mitigated the potential adverse impact of emotional dissonance on mental health. METHODS: In 2019, 1426 home-care workers from 130 organizational units were surveyed, with follow-ups after 8 and 14 months. Prospective associations between emotional dissonance (the Frankfurt Emotion Work Scales) and mental distress (Hopkins Symptom Checklist, HSCL-5), including interactions between emotional dissonance and leadership behaviors (Nordic Questionnaire for Psychological and Social Factors at Work), were determined using lagged linear mixed models. RESULTS: Emotional dissonance was positively associated with mental distress (adjusted P<0.05), whereas supportive, empowering, and fair leadership were negatively associated with mental distress (adjusted P<0.05). All three investigated sources of leadership behaviors moderated the direct association between emotional dissonance and mental distress (adjusted P<0.05). Emotional dissonance and mental distress were reciprocally related; an increase in either will heighten the level of the other. Leadership behaviors did not moderate the reversed association between emotional dissonance and mental distress (adjusted P>0.05). CONCLUSIONS: Supportive, empowering, and fair leadership buffers the association of emotional dissonance on mental distress. Strategic interventions that enhance the quality of leadership may help prevent mental distress among employees in professions with emotionally demanding tasks.